Research on New Roadside Filling Materials and Engineering Application - Li, Yabin (International Journal of Materials Science and Technology Studies, 2025)
To solve the problems of high labor intensity, and difficulty in controlling the quality of traditional filling materials filling systems, a one-component lane-side filling material with better load-bearing performance has been developed with corresponding filling equipment and process. In order to grasp the engineering performance of the filling material, orthogonal experimental method was adopted to test the basic performance of the bearing layer material, and the influence of various factors such as water-cement ratio and additives on the initial and final solidification time, reaction temperature and compressive strength of the slurry was investigated through the method of analysis of extreme difference. The results show that: the water-cement ratio has a greater impact on the four performance indicators; the mixing of appropriate amount of quick-setting agent can accelerate the slurry setting rate and reaction temperature; the mixing of early-strength agent and fibre can improve the early compressive strength and toughness of the specimen; comprehensive analysis of the third group of specimens under the load-bearing layer materials with quick-setting, early-strength characteristics, setting time of 9 minutes or less, the maximum compressive strength of 23.3MPa. At the same time, after the simulation test of the specimen with different support schemes, it was found that the integrity and stability of the filling body was improved under the joint restraint of tensile reinforcement, steel ladder beams and reinforcing mesh in the specimen of group D-4. The final on-site monitoring results show that: the displacement of the roadway surface increases after the roof collapses, in which the maximum amount of roof subsidence is 139mm, and the maximum amount of the two gangs approaching is 40mm, and the hollow area tends to be stable under the support of the filling body after compaction, which will ensure the safety of the next working face when it is being mined back.